The Relationship Between Emotional Intelligence, Self Efficacy and Prosocial Behaviour on interpersonal Conflic Management - Gaol, Marieta (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2018)
This study aimed to determine influence of emotional intelligence, self efficacy and prosocial behaviour on interpersonal conflic management of Guidance and Counseling student at University of Yogyakarta. This research method is quantitative with an ex-post facto type which takes a sample by using proportional random sampling technique. The sample consisted of 40 students of Universitas Negeri Yogyakarta, 126 students of Ahmad Dahlan University, 38 students of Sanata Dharma University, 66 students of PGRI University Yogyakarta, 21 students of Yogyakarta University of Technology, 5 students of Mercu Buana University Yogyakarta and 39 students of IKIP PGRI Wates who were all students of Guidance and Counseling semester IV. Data of emotional intelligence, self efficacy, prosocial behaviour and interpesonal conflic management is taken by using scale. Reliability Test used technique of Cronbach's alpha, obtained p=0.929 for emotional intelligence variable, p=0.917 for self efficacy variable, p=0.915 for prosocial behaviour variable, and p=0.849 for variable of interpersonal conflic management. There was a positive and significant correlation between emotional intelligence, self efficacy and prosocial behaviour and interpersonal conflic management, with correlation cooficient 0.559, obtained p=0.000 and effective contribution equal to 31.3%